Determinating full parameters of U-matrix for reconfigurable Boson sampling circuits using machine learning - Wan, L. X. (2020)
A method of tuning a reconfigurable silicon photonic circuit into an arbitrary unitary operator with machine learning was proposed to bypass the traditional phase-voltage calibration process and make the prediction of applied heating voltage directly.